Paleoenvironmental humanities: Challenges and prospects of writing deep environmental histories. (21st June 2020) - Hussain, S.T.; Riede, F.
Abstract: Environmental uncertainty, climate change, and ecological crisis loom large in the present and permeate scenarios of potential futures. To understand these predicaments and prepare for potentially catastrophic scenarios, there have been repeated calls to explore the diverse human–climate relations of human societies in the past. The archeological record offers rich datasets on human–environment articulations reflected in artifacts, ecofacts, and their relational entanglements. Much of these human–environment conjugations are, in the absence of written records, only accessible archeologically, yet that discipline has played little role in the "environmental turn" of the humanities or the climate change debate. In an effort to articulate archeological research traditions with these concerns, we frame the notion of the paleoenvironmental humanities (pEH): a deep‐time training ground for current ideas and theories on the interrelationship of human behavior, climate, and environmental change. The key objective of the pEH is to offer a rejoinder between ecological reductionism and the adoption of full‐scale environmental relativism, opening up new interpretive and comparative terrain for the examination of human–climate relations. We probe the potential of this perspective by drawing on insights from Pleistocene archeology. The long‐term temporalities of the Pleistocene, we argue, promote alternative imaginaries of the human–climate nexus and draw attention to similarly long‐term futures. We end our proposal with a reflection on the responsibility of archeological practitioners to balance hopeful narratives of human adaptability with those of societal collapse, countering the emergent linkage between climate skepticism and right‐wing nationalism, and to bring such issues to public attention. This article is categorized under: Climate, History, Society, Culture > Disciplinary Perspectives Abstract : The palaeoenvironmental humanities in a nutshell. Human deep history in articulation with patterns and processes of climatic, environmental and ecological change.